Do Sustainability Practices Drive Financial Performance? Evidence from Indonesia’s Energy Sector (2022-2024) - Lathifa Adilla Salsa; Taufeni Taufik; Riska Natariasari (Politeknik Ganesha Medan, 2026)
The relationship between sustainability practices and financial performance remains an important issue, particularly in the energy sector, which is associated with high environmental risks. However, previous studies have reported inconsistent findings, especially in developing countries. This study aims to examine whether sustainability practices influence the financial performance of energy sector companies in Indonesia. The study employs secondary data obtained from energy companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, with a sample of 37 companies selected using purposive sampling. Data were analyzed using multiple linear regression with IBM SPSS Statistics version 27. The results indicate that environmental performance has a significant positive effect on financial performance, whereas green strategy and corporate social responsibility do not have a significant effect. This study contributes to the literature by demonstrating that not all sustainability practices lead to improved financial performance. The findings imply that companies should prioritize enhancing their environmental performance as a strategic effort to improve financial performance.